Kingdom of Morocco : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) reviews Morocco's public sector financial management system, largely based on the French system that separates accounting practices from services organization, and from the initial expenditure control to the latter jurisdictional control. The Moroccan system appears largely robust, characterized by legal institutions; however, this seemingly, poses delays affecting the relation between public expenditures, and its results. Given these apparent weaknesses, the Government fostered reforms to modernize public administration, and improve services delivery. Recommendations included in this CFAA to improve public sector efficiency, address actions to improve budget preparation, and to formally standardize budgetary information to Parliament. Budget implementation should be made public, supported by legislation, while improved ministerial support should be ensured in human resources expenditures, and management; similarly, information related to investment payments should be improved, and itemized. Public expenditures control should be developed, ensuring performance in parallel to public spending, and, the role of ministerial inspections should be reinforced, through a regulatory framework, and enforcement of recommendations.